Judy Moody predicts the future - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2003)
After Judy obtains a mood ring, she tries to convince herself and her third-grade classmates that she can predict the future.
G2
Keywords: Prophecies -- Fiction; Rings -- Fiction; Schools -- Fiction